2018
DOI: 10.29249/selcuksbmyd.349338
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık İşletmelerinde Müşteri Odaklı Pazarlama Anlayışı İle Hizmet Kalite Algısı Arasındaki İlişki; Bir Hastane Örneği

Abstract: Müşteri odaklılık, işletmelerin yürütmekte olduğu pazarlama faaliyetlerinde müşteri istek ve ihtiyaçlarını göz önünde bulunduran bir pazarlama anlayışıdır. Diğer sektörlerde olduğu gibi sağlık sektöründe müşteri memnuniyeti ve hizmet kalitesinin önemi her geçen gün artmakta, müşteri memnuniyetinin sağlanması çalışanların müşteri odaklı hizmet vermeleriyle mümkün olmaktadır. Bu araştırmanın amacı; sağlık sektöründe çalışanların müşteri odaklı pazarlama anlayışı ile hastaların müşteri memnuniyeti ve hizmet kalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…However, Hassan's (2006) findings on the variables of business excellence supported our study results. Soysal and Koçoğlu's (2018) study showed that healthcare providers' understanding of customer focus was higher than the average attitude of patients.…”
Section: Discussionmentioning
confidence: 90%
“…However, Hassan's (2006) findings on the variables of business excellence supported our study results. Soysal and Koçoğlu's (2018) study showed that healthcare providers' understanding of customer focus was higher than the average attitude of patients.…”
Section: Discussionmentioning
confidence: 90%
“…The personnel in the service sector, who are in constant contact with customers, place great importance on customer orientation. It is expected that this continuous customer interaction will lead to increased customer satisfaction and the potential for loyal customers [25] .…”
Section: Customer Orientationmentioning
confidence: 99%
“…Algılanan hizmet kalitesi ile ilgili daha önce yapılan çalışmalar incelendiğinde sağlık hizmetleri (Yeşildağ ve Ulusoy, 2021;Soysal ve Koçoğlu, 2018;Çağlıyan, 2017;Sezer, Durmuş ve Bebik, 2020;Tarcan ve Balçık, 2020;Aydın ve Yıldırım, 2012;Songur, Turan ve Songur, (2017), yeme içme hizmetleri (Şeker, Yavuz ve Unur, 2016;Tuncer, 2017), ulaşım hizmetleri (Yao ve Ding, 2011;Ingaldi, 2016;Yıldız ve Erdil, 2013;Kazançoğlu, 2011;Çatı, 2003;Köseoğlu ve Kitapçı, 2022;Yapraklı ve Ünalan, 2016;Pekkaya ve Akıllı, 2013;Uslu, 2013), eğitim-öğretim hizmetleri (Czajkowska & Ingaldi, 2021;Maksüdünov, Çavuş ve Eleren, 2016;Arslantürk, 2010), konaklama hizmetleri (Li, 2010;Yapraklı ve Sağlık, 2010;Aşık, 2016) bankacılık hizmetlerinde (Nguyen, Chaipoopirutana & Combs, 2011;Fragoso ve Espinoza, 2017;Vanpariya & Ganguly, 2011;Işık, Akbolat ve Ünğan, 2013;Öncü, Kutukız ve Koçoğlu, 2010;Bekki, 2017) ve özel güvenlik hizmetleri (Çavdar ve Gürbüzkol, 2016) gibi farklı hizmet sektöründe SERVPERF ölçeği ile yapılmış pek çok çalışmanın bulunduğu görülmektedir.…”
Section: Empatiunclassified